ACTR-39. TWO-YEAR RESULTS OF THE INTELLANCE 2/EORTC TRIAL 1410 RANDOMIZED PHASE II STUDY ON DEPATUX–M ALONE, DEPATUX-M COMBINED WITH TEMOZOLOMIDE (TMZ) AND EITHER TMZ OR LOMUSTINE IN RECURRENT EGFR AMPLIFIED GLIOBLASTOMA (NCT02343406. (5th November 2018) - van den Bent, Martin; French, Pim; Eoli, Marica; Sepulveda, Juan; Walenkamp, Annemiek; Frenel, Jean-Sebastian; Franceschi, Enrico; Clement, Paul; Weller, Michael; de Heer, Iris; Looman, Jim; Dey, Jyotirmoy; et al.
Abstract: BACKGROUND: Depatux-M is an antibody-drug-conjugate consisting of an antibody (ABT-806) specific to the activated conformation of EGFR bound to the toxin monomethylauristatin-F. In the primary analysis on EORTC 1410 we reported a trend (p = 0.06) towards improved overall survival (OS) in patients with EGFR-amplified (amp) recurrent glioblastoma treated with Depatux-M in combination with temozolomide. METHODS: Eligible were patients with centrally confirmed EGFRamp glioblastoma at 1st recurrence after temozolomide chemo-irradiation. Patients were randomized to either a) Depatux-M 1.0 mg/kg every 2 weeks intravenously, or b) the same treatment combined with temozolomide 150–200 mg/m2 day 1–5 every 4 weeks, or c) either lomustine or temozolomide (TMZ/LOM) depending on the time of relapse. Primary endpoint was OS. Pharmacokinetic sampling was part of the study design, all samples were used to calculate the Depatux-M average concentration during course 1 (CavgC1). The level of EGFRamp was re-analysed using next generation sequencing. RESULTS: In February 2018, an updated OS comparison performed after 220 observed deaths of Depatux-M in combination with TMZ versus TMZ/LOM using log-rank test and cox models stratified by stratification factors at randomization showed a HR of 0.68 (95%CI [0.48, 0.95]; p = 0.024) and 1-year OS rates of 40% versus 28%. In multivariate analysis CavgC1 was a significant predictor for OS (HR 0.96, 95% CI [0.93, 0.98], p = 0.0013). In Depatux-M treated patients, EGFR status (high vs low level amplification) did not correlate with OS. At the meeting the follow-up from Aug 2018 will be presented, obtained more than 24 months after the end of accrual. CONCLUSION: This updated OS analysis of Depatux-M in combination with temozolomide confirmed the OS improvement in EGFRamp recurrent glioblastoma. In Depatux-M treated patients, higher drug levels during course 1 were associated with improved OS, but high levels of EGFR amplification at first diagnosis were not.